Species differences in immune‐mediated CNS tissue injury and repair: A (neuro)inflammatory topic. Issue 4 (14th November 2019) - Healy, Luke M.; Yaqubi, Moein; Ludwin, Samuel; Antel, Jack P.
Abstract: Cells of the adaptive and innate immune systems in the brain parenchyma and in the meningeal spaces contribute to physiologic functions and disease states in the central nervous system (CNS). Animal studies have demonstrated the involvement of immune constituents, along with major histocompatibility complex (MHC) molecules, in neural development and rare genetic disorders (e.g., colony stimulating factor 1 receptor [CSF1R] deficiency). Genome wide association studies suggest a comparable role of the immune system in humans. Although the CNS can be the target of primary autoimmune disorders, no current experimental model captures all of the features of the most common human disorder placed in this category, multiple sclerosis (MS). Such features include spontaneous onset, environmental contributions, and a recurrent/progressive disease course in a genetically predisposed host. Numerous therapeutic interventions related to antigen and cytokine specific therapies have demonstrated effectiveness in experimental autoimmune encephalomyelitis (EAE), the animal model used to define principles underlying immune‐mediated mechanisms in MS. Despite the similarities in the two diseases, most treatments used to ameliorate EAE have failed to translate to the human disease. As directly demonstrated in animal models and implicated by correlative studies in humans, adaptive and innate immune constituents within the systemic compartment and resident in the CNS contribute to the disease course of neurodegenerative and neurobehavioral disorders. The expanding knowledge of the molecular properties of glial cells provides increasing insights into species related variables. These variables affect glial bidirectional interactions with the immune system as well as their own production of "immune molecules" that mediate tissue injury and repair. Abstract : Poor recapitulation of human neuroinflammatory disease by animal models; Caused by species differences in the immune and glial systems Resulting from >75 million years of evolutionary divergence, unique environmental niches, evolutionary pressures, and aggressive inbreeding.